Characterization of endo and ecto parasitism in equids slaughtered for human consumption: The Villa Rosa case. Santander, Colombia - Uribe, Nelson; Betancourt, Antonio; Hernández, Darwin (Spei Domus, 2019)
Introduction: To identify endo and ectoparasites in equids slaughtered at the Villa Rosa slaughter house in Piedecuesta, Santander, between October and December 2015. Metodology: For ecto and hemoparasites studies, 83 equids were employed, and 75 for gastrointestinal parasites. Ectoparasites were collected directly from the skin and hemoparasites by blood culture, Woo, wet preparations, stained smears and Knott Technique. Gastrointestinal parasites were studied by Mc Master and Sedimentation-Flotation techniques, as well as feces cultivation and helminthological necropsy. Results: Anocentor nitens ticks were found on 31,32 % of the equids and 8,43 % had mixed infestation with Amblyomma cajennense s.l.. The louse Haematopinus asini was collected from one animal. Except for the presence of Setaria equina microfilariae, in 7,2 % of the samples, no hemoparasites were detected with the parasitological methods employed. “Strongylid type” eggs were found in 88% of the samples, Dictyocaulus sp. in 6,6 %; Parascaris sp. in 5,3 %; Oxyuris sp. in 5,3 %; Strongyloides sp. in 1,33 % and Anoplocephala sp. in 9.3%. Culturing of feces yielded only 12 L3 larvae of the Cyathostominae or “Small Strongyles” group and one of Trichostrongylus axei. Helminthological necropsies recovered adults of Habronema megastoma, Setaria equina, Oxyuris equi, Strongylus spp., Triodontophorus, Cyathostominae and Anoplocephala perfoliata. Conclusions: Parasitisms by ticks, large and small strongyles and tapeworms are common in horses slaughtered in Piedecuesta, Santander. Serologic and molecular tests are recommended to detect hemoparasites in future studies.